Relationship between Stress Levels and UPF Consumption on Blood Pressure in Obese Adolescents - Zahrina Fildza Luthfiana Sutomo; Yulia Lanti Retno Dewi; Lusi Oka Wardhani (GLOBAL HEALTH SCIENCE GROUP, 2025)
Adolescent obesity is a growing global health problem, with the risk of developing hypertension due to activation of the sympathetic nervous system (SNS) and sodium regulation. Psychosocial stress and unhealthy diets, including consumption of Ultra-Processed Foods (UPF), contribute to increased blood pressure. UPF high in sodium, fat, and sugar are associated with hypertension, while stress can trigger emotional eating, increasing consumption of high-calorie foods. Adolescent diets tend to be low in fiber and high in UPF, supported by the school environment. This study aims to analyze the relationship between stress levels and UPF consumption on blood pressure in obese adolescents to understand the risk factors for hypertension in this group. This study used an analytical observational design with a cross-sectional approach. A sample of 75 students was selected by purposive sampling. Data were collected through interviews and measurements, then analyzed using SPSS version 29 statistically. The majority of respondents were 16 years old, male, with high UPF consumption. UPF consumption was significantly associated with diastolic blood pressure (p=0.036, r=0.255). Stress level was not significantly associated with blood pressure (p>0.05, r=0.1–0.2). Stress levels did not have a significant relationship with either systolic or diastolic blood pressure. UPF consumption was not significantly related to systolic blood pressure, but UPF consumption was significantly related to diastolic blood pressure.